Shariah Sebagai Metodologi Problem Solver Catatan atas Pemikiran Ziauddin Sardar - Aji Damanuri (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2013)
Islamic law moves from ilatul hukmi to maqashid al Shariah is a remarkable development. Where the determination of the law is not only judged by the cause but also the purpose of enacting a law. Although experiencing methodological developments, but whether these changes provide what is expected by the people as mukalifun? Or is it just a method that does not give any effect except the same taklif to the people. Ziauddin Sardar responded to this by proposing the idea that Maqashid al Shariah should be able to become a problem solver for the people. This paper presents Ziauddin Sardar's thoughts that propose Shariah is not only methodologically reliable in istinbat law but also able to provide solutions to the problems of the people.